2013
DOI: 10.4274/npa.y6336
|View full text |Cite
|
Sign up to set email alerts
|

Travma Sonrası Bilişler Envanteri’nin (TSBE) Türkçe Formu’nun Klinik Olmayan Örneklemde Psikometrik Özellikleri

Abstract: Re cei ved/Ge liş ta ri hi: 15.10.2011 Ac cep ted/Ka bul ta ri hi: 06.01.2012 © Arc hi ves of Neu ropsy chi atry, pub lis hed by Ga le nos Pub lis hing / © Nö rop si ki yat ri Ar şi vi Der gi si, Ga le nos Ya yı ne vi ta ra f›n dan ba s›l m›fl t›r. ABS TRACTBackground: Cognitive theories of posttraumatic stress disorder have increasingly been recognised. The Posttraumatic Cognitions Inventory is a promising self-report instrument to assess negative cognitions associated with posttraumatic distress. Method: In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Therefore, if the modification indices indicated that an item cross-loaded onto two factors, an exploratory factor analysis was conducted to determine the degree of cross-loadings. (d) In an effort to increase external validity, if an item had been removed in several previously replicated CFAs (i.e., Beck et al, 2004; Daie-Gabai et al, 2011; Gulec et al, 2013; Hyland et al, 2015; Muller et al, 2010; Su & Chen, 2008; van Emmerik, Schoorl, Emmelkamp, & Kamphuis, 2006) then the item was considered for removal. Investigators on this study met to discuss all content and statistical issues to reach consensus about the overall and subscale content and items.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, if the modification indices indicated that an item cross-loaded onto two factors, an exploratory factor analysis was conducted to determine the degree of cross-loadings. (d) In an effort to increase external validity, if an item had been removed in several previously replicated CFAs (i.e., Beck et al, 2004; Daie-Gabai et al, 2011; Gulec et al, 2013; Hyland et al, 2015; Muller et al, 2010; Su & Chen, 2008; van Emmerik, Schoorl, Emmelkamp, & Kamphuis, 2006) then the item was considered for removal. Investigators on this study met to discuss all content and statistical issues to reach consensus about the overall and subscale content and items.…”
Section: Methodsmentioning
confidence: 99%
“…Since the development of the PTCI there have been several additional examinations of its psychometric characteristics using both the English and translated versions. The original and translated versions have been tested in adult (Beck et al, 2004; Daie-Gabai, Aderka, Allon-Schindel, Foa, & Gilboa-Schechtman, 2011; Gulec, Kalafat, Boysan, & Barut, 2013; Muller et al, 2010; Su & Chen, 2008) and adolescent (Hyland et al, 2015) samples with various types of trauma survivors (e.g., motor vehicle accident survivors, interpersonal trauma survivors). Results of confirmatory factor analyses (CFAs) have varied across studies and different items have been removed to achieve the best model fit, which may indicate variation in methods and samples.…”
mentioning
confidence: 99%
“…Respondents are asked to rate each item on a 7-point Likert type scale, ranging from 1 (''totally disagree'') to 7 (''totally agree''). The Turkish version of the scale was demonstrated to have excellent reliability and validity (Gulec, Kalafat, Boysan, & Barut, 2013).…”
Section: Posttraumatic Cognitions Inventory (Ptci)mentioning
confidence: 99%